Herbage accumulation and nutritive value of cultivar Mulato II, Congo grass, and Guinea grass cultivar C1 in a subhumid zone of West Africa - Nouhoun, Z.; Tidiane, T.C.; Epiphanie, S.T.B.P.; Ayantunde, Augustine A.; Prasad, Kodukula V.S.V.; Blümmel, Michael; Balehegn, M.; Ríos, E.F.; Dubeux, J.C.B.; Boote, Kenneth J.; Adesogan, Adegbola T. (Wiley, 2022)
Despite a long history promoting improved forages, their adoption in sub‐Saharan Africa remains limited. Identifying cultivars and developing the right agronomic practices suited to specific forage systems can help reduce the feed gap in this region. This 2‐yr study was performed under rainfed conditions at the Institute of Environment and Agricultural Research research station in Farakoba, Burkina Faso. Treatments included two planting methods (continuous rows 40‐cm apart vs. open pits spaced 40 × 40 cm) and three perennial grasses: Urochloa spp. cultivar Mulato II, Congo grass [U. ruziziensis (R. Germ. and C.M. Evrard) Crins] and Guinea grass [Megathyrsus maximus (Jacq.) B.K. Simon & S.W.L. Jacobs] cultivar C1. The experimental design was a randomized complete block under a split plot treatment arrangement, and planting method was the main plot (3 × 7 m) and the grass varieties the subplots (3 × 3 m). Plots were established in August 2018, and herbage accumulation (HA) and nutritive value (NV) were measured in 2018 and 2019. Regardless of planting method, Mulato II had greater total herbage mass (26 Mg ha–1) after 2 yr than did Congo grass (15 Mg ha–1) and cultivar C1 (12 Mg ha–1) (p ≤ .05). Mulato II had the greatest crude protein (170 g kg–1), in vitro digestible organic matter (635 g kg–1), and metabolizable energy (89 MJ kg–1), and least neutral detergent fiber (537 g kg–1) concentrations, as compared to other cultivars (p ≤ .05). Both HA and NV were greater (p ≤ .001) for open pits spaced 40‐cm apart than the continuous rows for all cultivars, indicating that this planting method seems more appropriate to establish forage grasses. Mulato II showed potential to increase forage productivity and NV in Burkina Faso.